PRAGMATIC INTENTION TO ATTRACT READERS’ ATTENTION IN ENGLISH AND KARAKALPAK LITERATURE - Khadjieva, D.T.; Kurbanbayeva, G. (SCIENCE and SOCIETY, 2022)
The article deals with the problem of linguopragmatic text analysis. It is an attempt in investigating the problem of pragmatic intentions and to be exact pragmatic intention of “to attract attention” (attention-compelling intention). The pragmatic intention “to attract the readers' attention’' is realized in fictional works by the means of “deautomatization”. To these means we can refer various occasional transformations of words (simple, derivative and compound words), stylistic devices, phraseological units which were studied on the basis of analysis taken from literary works of English and Karakalpak writers. Having analyzed more than 200 examples from literary texts in English and Karakalpak languages we’ve come to conclusion that pragmatic intention to attract reader’s attention is realized in literary texts with the help of occasionalizms and convergence of stylistic devices.
Keywords: linguopragmatics; pragmatic intentions; “to attract attention” attention-compelling intention; an occasionalism; stylistic effect